An integrative multiomic network model links lipid metabolism to glucose regulation in coronary artery disease - Ariella T. Cohain (Nature Portfolio, 2021)
Some cholesterol-lowering drugs can increase the risk of type 2 diabetes, but the mechanism behind this is not fully understood. Here the authors show that there is a single genetic regulatory module that influences both cholesterol levels and glucose levels, providing a link between cholesterol levels and diabetes.